2019
DOI: 10.3390/jcm8091362
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients Showing Discrepancy Between Bruch’s Membrane Opening-Minimum Rim Width and Peripapillary Retinal Nerve Fiber Layer Thickness

Abstract: Background: To investigate clinical characteristics of patients showing discrepancy between Bruch’s membrane opening minimum rim width (BMO-MRW) and peripapillary retinal nerve fiber layer (RNFL) thickness. Correlation with the visual field (VF) was also inspected. Methods: In this prospective, cross-sectional study, 106 eyes (106 subjects) showing normal BMO-MRW classification but abnormal RNFL classification were included. All patients underwent confocal scanning laser ophthalmoscopy, spectral-domain optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…A discrepancy between the clinical disc margin based on fundus photography and the BMO-based disc margin was noted in our study. It has been described in several previous studies, and initially by Chauhan et al ( 7 , 11 , 14 ). The discrepancy was also noted in our previous study, “Characteristics of Patients Showing Discrepancy Between Bruch’s Membrane Opening-Minimum Rim Width and Peripapillary Retinal Nerve Fiber Layer Thickness” ( 14 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A discrepancy between the clinical disc margin based on fundus photography and the BMO-based disc margin was noted in our study. It has been described in several previous studies, and initially by Chauhan et al ( 7 , 11 , 14 ). The discrepancy was also noted in our previous study, “Characteristics of Patients Showing Discrepancy Between Bruch’s Membrane Opening-Minimum Rim Width and Peripapillary Retinal Nerve Fiber Layer Thickness” ( 14 ).…”
Section: Discussionmentioning
confidence: 87%
“…Latest studies have shown that BMO-MRW demonstrated better diagnostic performance in glaucoma than preexistent NRR parameters ( 11 13 ). In our previous study, we reported that BMO-MRW might reveal normal color code classification, whereas the RNFL showed abnormal color code classification in cases of large discs and myopia ( 14 ). This previous study of ours suggested the clinical usefulness of BMO-MRW in early glaucoma or GS, particularly in cases of large disc and myopia when the diagnosis is difficult because conventional color code classification of RNFL may display false-positive results.…”
Section: Introductionmentioning
confidence: 97%
“…34,35 Such reductions were also identified in the global average thickness retinal fiber layer (RNFL) or peripapillary retinal nerve fiber layer (pRNFL) in the non-temporal topographic profiles in eyes with high myopia, [36][37][38] while RNFL was with significantly thicker in the temporal quadrant in eyes with high myopia than that in eyes with low myopes. 39,40 Additionally, the outer segment of receptors layer has been reported to be thicker in the high myopic group compared with the normal group. 41 The expression profile of HNRNPH1 in human retina provides evidence that it may be specifically affected the retinal cells in patients with high myopia.…”
Section: Discussionmentioning
confidence: 99%
“…The ganglion cell‐inner plexiform layer (GC‐IPL) thickness has been proved to be significantly thinner in highly myopia eyes than normal eyes or low myopia 34,35 . Such reductions were also identified in the global average thickness retinal fiber layer (RNFL) or peripapillary retinal nerve fiber layer (pRNFL) in the non‐temporal topographic profiles in eyes with high myopia, 36–38 while RNFL was with significantly thicker in the temporal quadrant in eyes with high myopia than that in eyes with low myopes 39,40 . Additionally, the outer segment of receptors layer has been reported to be thicker in the high myopic group compared with the normal group 41 .…”
Section: Discussionmentioning
confidence: 99%
“…BMO-MRW also shows a better structure-function relationship in glaucoma than other pre-existing peripapillary RNFL and parameters of confocal scanning laser ophthalmoscope [ 10 , 11 , 12 , 13 ]. We have previously described a disagreement between BMO-MRW and RNFL in classification analysis of color-codes [ 14 ]. At early glaucomatous stage, structural changes are minimal.…”
Section: Introductionmentioning
confidence: 99%